2018
DOI: 10.1093/abm/kax067
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Writing Intervention Improves Quality of Life Among Chinese-American Breast Cancer Survivors: A Randomized Controlled Trial

Abstract: Background Expressive writing interventions are shown to confer health benefits for Caucasian cancer survivors. However, few studies reported improved quality of life or studied ethnic minorities. Purpose The study evaluated whether a culturally sensitive expressive writing intervention improved quality of life. Methods Chinese-speaking breast cancer survivors (n = 136) in the USA were randomly assigned to one of three conditions to write three 30-min weekly essays: a cancer-fact condition to write about facts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…For example, Tai Chi is a moderate form of exercise that have been found to have positive effects on self‐esteem, mood, and quality of life among breast cancer survivors . Similarly, writing‐based interventions such as expressive writing have been found to improve quality of life among Chinese American breast cancer survivors, and those with higher levels of AEE may particularly benefit from this intervention …”
Section: Discussionmentioning
confidence: 99%
“…For example, Tai Chi is a moderate form of exercise that have been found to have positive effects on self‐esteem, mood, and quality of life among breast cancer survivors . Similarly, writing‐based interventions such as expressive writing have been found to improve quality of life among Chinese American breast cancer survivors, and those with higher levels of AEE may particularly benefit from this intervention …”
Section: Discussionmentioning
confidence: 99%
“…We found that the Facebook campaign was successful in recruiting a sample of Latinx and East Asian cancer survivors with different cancer diagnoses from various geographic regions of the United States. Latinx and East Asian cancer survivors recruited from Facebook enjoyed sharing their cancer experiences and endorsed their interest in participating in future psychosocial intervention studies ranging from internet-based focus groups to private emotional disclosure through writing or voice-recording (e.g., expressive writing interventions [16]). Furthermore, we found that all but three (88%) participants have access to smartphones, and thus can participate in internet-based or mobile-based psychosocial interventions that have become increasingly popular in recent years [17].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese culture is a "relational culture" [42]; therefore, we took a relational approach to engage community members. We approached recruitment as an opportunity to build rel ationships with potential participant s. Community research staff acted as relationship builders and recruiters, reducing the power differential that often exists between academic researchers and research participants, particularly for an immigrant sample with limited English ability [43]. Recruiters' first priority was to establish an environment in which individuals felt personally cared for.…”
Section: Two Illustrative Case Studiesmentioning
confidence: 99%